2019
DOI: 10.4314/jasem.v23i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Third Cemetery Location on the Quality of Domestic and Groundwater Resources in Benin City, Nigeria

Abstract: The present study investigates impact of burial practices on water quality in Benin City, Nigeria by collecting groundwater samples from boreholes located by the peripheral area of Third Cemetery in Benin City and a reference site approximately 4 km away using standard methods. With the exception of SO4, CaCO3, Fe and DO, the concentrations of other parameters were higher in water samples obtained from the peripheral area of Third Cemetery than that from the reference site. Principal component analysis (PCA) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Results obtained from a study conducted at the Zandfontein Cemetery in the Tshwane Municipality in South Africa indicated that a number of metals, associated with burial material, were concentrated at the cemetery, and not found in areas away from the cemetery (Jonker and Olivier, 2012). Measures and awareness need to be put in place to ensure that corpses and burials do not contribute to people consuming polluted water, contaminated by decomposition of the deceased (Idehen and Ezenwa, 2019). These landfills are defined by solid matter, as well as leachate composed of organic and inorganic substances and pathogenic bacteria (Yusmartini, et al 2013).…”
Section: Cemeteriesmentioning
confidence: 99%
“…Results obtained from a study conducted at the Zandfontein Cemetery in the Tshwane Municipality in South Africa indicated that a number of metals, associated with burial material, were concentrated at the cemetery, and not found in areas away from the cemetery (Jonker and Olivier, 2012). Measures and awareness need to be put in place to ensure that corpses and burials do not contribute to people consuming polluted water, contaminated by decomposition of the deceased (Idehen and Ezenwa, 2019). These landfills are defined by solid matter, as well as leachate composed of organic and inorganic substances and pathogenic bacteria (Yusmartini, et al 2013).…”
Section: Cemeteriesmentioning
confidence: 99%
“…In situ parameters including; electrical conductivity (EC), hydrogen ion concentration (pH) and total dissolved solids (TDS) were determined with the aid of Extech meter probes (Exstik II). In the laboratory, the analysis of other parameters including total suspended solids (TSS), calcium, magnesium, sulphate, nitrate, phosphate, chloride, calcium carbonate (CaCO 3 ), sodium, potassium, lead, copper, chromium, iron, zinc, manganese, cadmium, nickel, mercury, dissolved oxygen (DO), biochemical oxygen demand (BOD 5 ), chemical oxygen demand (COD) were done using standard methods adopted from APHA (1998); (Radojevic &Bashkin, 1999, Idehen, & Ezenwa, 2019.…”
Section: Field and Laboratory Analysesmentioning
confidence: 99%
“…The primary sources of pollution in cemeteries, according to Guttman et al [1], are materials used to manufacture coffins and embalming fluids. Toxic metals (e.g., Fe, Cu, Ni, Pb, and Zn) are released into the soil by varnishes, sealants, metal handles, and decorations found on wooden coffins [11,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%